Project management in the oil and gas industry - El-Reedy, Mohamed A. (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2016)
Oil and gas projects have special characteristics that need a different technique in project management. The development of any country depends on the development of the energy reserve through investing in oil and gas projects through onshore and offshore exploration, drilling, and increasing facility capacities. Therefore, these projects need a sort of management match with their characteristics, and project management is the main tool to achieving a successful project. Written by a veteran project manager who has specialized in oil and gas projects for years, this book focuses on using practical tools and methods that are widely and successfully used in project management for oil and gas projects. Most engineers study all subjects, but focus on project management in housing projects, administration projects, and commercial buildings or other similar projects. However, oil and gas projects have their own requirements and characteristics in management from the owners, engineering offices, and contractors' side. Not only useful to graduating engineers, new hires, and students, this volume is also an invaluable addition to any veteran project manager's library as a reference or a helpful go-to guide. Also meant to be a refresher for practicing engineers, it covers all of the project management subjects from an industrial point of view specifically for petroleum projects, making it the perfect desktop manual. Not just for project managers and students, this book is helpful to any engineering discipline or staff in sharing or applying the work of a petroleum project and is a must-have for anyone working in this industry.
Keywords: Petroleum industry and trade -- Management.; Project management.; elektronické knihy; electronic books